Clinical communication in inflammatory bowel disease: a systematic literature review protocol. Issue 11 (4th November 2020) - Karimi, Neda; Moore, Alison Rotha; Lukin, Annabelle; Kanazaki, Ria; Williams, Astrid-Jane; Connor, Susan
Abstract : Introduction: Evidence regarding effective communication between clinicians and patients with inflammatory bowel disease (IBD) is limited. Studies that investigate clinical communication in IBD are much fewer in number than studies that investigate the perceptions of patients and clinicians about communication in clinical encounters. The current review aims to identify, organise and summarise systematically what is currently known about (1) the characteristics of interactions between clinicians who manage IBD and patients with IBD, and (2) how clinical discussion affects health outcomes in IBD. Methods and analysis: Scopus, PubMed, Embase, Communication Abstracts, Health & Society, Linguistics and Language Behavior Abstracts and PsycINFO will be systematically searched for studies that investigate the characteristics of IBD clinical interactions during recorded consultations, from earliest available dates within each database to May 2020. A specifically developed quality assessment tool, grounded in linguistic theory, will be used to critically assess the evidence. In addition, a data extraction template will be developed and utilised to provide a description of the characteristics of IBD clinical communication as well as an estimation of its effect on health outcomes in a narrative synthesis. Ethics and dissemination: Ethical review and approval is not required for this systematic review as no primary data will be collected. The results will be published in peer-reviewed journals and presented at academic conferences. PROSPERO registration number: International Prospective Register of Systematic Reviews (PROSPERO) on 28 April 2020 (registration number: CRD42020169657).